1975
DOI: 10.1007/bf00222049
|View full text |Cite
|
Sign up to set email alerts
|

Satellite cells of the rat soleus muscle in the process of compensatory hypertrophy combined with denervation

Abstract: Compensatory hypertrophy was induced in the rat soleus muscle by sectioning the tendon of the ipsilateral gastrocnemius and plantaris muscle. Seven days after tenotomy of synergistic muscles, when soleus hypertrophy attains about 40%, the number of satellite cells (expressed as percentage of all muscle nuclei found in the same cross-sections) as revealed by electron microscopy, was increased from 5.8+/-0.06% in the normal soleus muscle to 16.6+/-1.26%. After four days' denervation of the soleus muscle the perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
2
1

Year Published

1978
1978
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 20 publications
1
33
2
1
Order By: Relevance
“…However, these studies have generated some controversy concerning the timing of increases of the number of SCs in denervated muscles. Despite the fact that several authors reported a marked increase in the number of SCs during the first week following denervation (Hanzlikova et al 1975;McGeachie and Allbrook 1978), a few other studies demonstrated such increases between 2 and 4 weeks after nerve transection (Ontell 1974;Snow 1983). These findings are in contrast to those obtained in our laboratory.…”
Section: Figurecontrasting
confidence: 99%
See 1 more Smart Citation
“…However, these studies have generated some controversy concerning the timing of increases of the number of SCs in denervated muscles. Despite the fact that several authors reported a marked increase in the number of SCs during the first week following denervation (Hanzlikova et al 1975;McGeachie and Allbrook 1978), a few other studies demonstrated such increases between 2 and 4 weeks after nerve transection (Ontell 1974;Snow 1983). These findings are in contrast to those obtained in our laboratory.…”
Section: Figurecontrasting
confidence: 99%
“…Since skeletal muscle SCs were discovered, the standard and most precise method for quantitative detection of these cells has been to electron microscopy (Hanzlikova et al 1975;Snow 1977Snow ,1983 …”
Section: Discussionmentioning
confidence: 99%
“…No morphological evidence of mitotic activity such as that reported in satellite cell nuclei [Shafiq et al, 1968;Moss and Leblond, 1971;Hanzlikova et al, 1975] was found in the myonuclei examined in this study. There also was no morphological evi dence to suggest that myonuclei budded off [Reznik, 1976], It is, therefore, postulated that the muscle fiber centrioles either repre sent remnants of mononucleated myogenic Fig-2.…”
Section: Resultscontrasting
confidence: 42%
“…Embryonic myosin has been observed in regions remote from sites of focal injury leading to the suggestion that newly fused satellite cells, the myoblast-like cells in skeletal muscle (Mauro, 1961) that supply myofiber nuclei for muscle regeneration (Snow, 1977), might be responsible for altering myosin expression in these undamaged regions, as well as in sites of injury (Stewart et al, 1989). Satellite cells also supply hypertrophying fibers with additional nuclei (Schiaffino et al, 1972;Hanzlikova et al, 1975;Seiden, 1976;Snow, 1990;Winchester et al, 1991;Winchester and Gonyea, 19921, raising the possibility that satellite cells play a role in altering myosin isoform expression in hypertrophying fibers. We have examined this notion in the present study.…”
Section: Introductionmentioning
confidence: 99%